System and method of traffic filtration at DDoS-attack detection - GUDOV NIKOLAY V; KORESHKOV DENIS E; KHALIMONENKO ALEXANDER A (2018)
The present disclosure discloses a system and method of traffic filtration at DDoS-attack detection. The present disclosure relates to a system and method for filtering network traffic to protect a server from a distributed denial-of-service (DDoS) attack, and computer readable storage medium having instructions for filtering network traffic to protect a server from a distributed denial-of-service(DDoS) attack. The described technique includes intercepting data from a network node to the computing device responsive to detecting a computing device is subject to a DDoS attack. The technique further includes determining one or more data transmission parameters based on the intercepted data, assigning a danger rating to the network node, and changing the danger rating of the network node based on application of a filter and on the data transmission parameters. The described technique limits a transmittal of data from the network node to the computing device if the resultant danger ratingof the network node exceed